2009
DOI: 10.1371/journal.pone.0007595
|View full text |Cite
|
Sign up to set email alerts
|

Fellatio by Fruit Bats Prolongs Copulation Time

Abstract: Oral sex is widely used in human foreplay, but rarely documented in other animals. Fellatio has been recorded in bonobos Pan paniscus, but even then functions largely as play behaviour among juvenile males. The short-nosed fruit bat Cynopterus sphinx exhibits resource defence polygyny and one sexually active male often roosts with groups of females in tents made from leaves. Female bats often lick their mate's penis during dorsoventral copulation. The female lowers her head to lick the shaft or the base of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 28 publications
(18 reference statements)
1
26
0
Order By: Relevance
“…38 Another example would be one of the most popular research articles published at Plos One 'Fellatio by fruit bats prolongs copulation time' . 39 To date, its Altmetric score is 489 and it achieved more than 362,461 views, 317 tweets from 268 users, with an upper bound of 1,139,028 followers, was considered by 410 Mendeley readers and featured in 32 scientific blogs. Yet it has been cited only 8 times in Web of Science and 10 times according to Scopus.…”
Section: Resultsmentioning
confidence: 99%
“…38 Another example would be one of the most popular research articles published at Plos One 'Fellatio by fruit bats prolongs copulation time' . 39 To date, its Altmetric score is 489 and it achieved more than 362,461 views, 317 tweets from 268 users, with an upper bound of 1,139,028 followers, was considered by 410 Mendeley readers and featured in 32 scientific blogs. Yet it has been cited only 8 times in Web of Science and 10 times according to Scopus.…”
Section: Resultsmentioning
confidence: 99%
“…It thus seems fitting that a new development involves females that deliver stimulation directly to the male genitalia during copulation. In Cyanopterus sphinx fruit bats, for example, females often lick the base of the male penis during intromission, and there is a positive relationship between this licking and the duration of copulation (Tan et al 2009). Licking may have antibiotic effects or other advantages, but there may also be some benefit in extending the duration of copulation, such as increased sperm transfer (Tan et al 2009).…”
Section: Females Stimulate the Male's Genitaliamentioning
confidence: 99%
“…In Cyanopterus sphinx fruit bats, for example, females often lick the base of the male penis during intromission, and there is a positive relationship between this licking and the duration of copulation (Tan et al 2009). Licking may have antibiotic effects or other advantages, but there may also be some benefit in extending the duration of copulation, such as increased sperm transfer (Tan et al 2009). Such potential benefits are suggested by yet another twist in the tale: In Pteropus giganteus flying foxes, males lick the female genitalia before and after copulation, and there is a positive relationship between the duration of precopulatory licking and the duration of copulation (Maruthupandian and Marimuthu 2013).…”
Section: Females Stimulate the Male's Genitaliamentioning
confidence: 99%
“…Additionally, oral sex performed by females on males (fellatio) is common in humans, though less common among non-human species. Tan et al (2009) documented that female short-nosed fruit bats (Cynopterus sphinx) that spend more time performing fellatio on a male also spend more time copulating with him, and Koelman et al (2000) found that a woman is less likely to experience preeclampsia if her regular partner ejaculates into her mouth-and especially if she ingests his semen-prior to conception. We suggest that researchers employ sperm competition theory to guide future work on oral sex.…”
Section: Oral Sexmentioning
confidence: 99%